2014
DOI: 10.1128/jcm.00237-14
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of the BD MAX MRSA Assay

Abstract: A comparison between the BD MAX MRSA and Xpert MRSA assays was performed using 239 nares samples. A 97.9% overall agreement between the two molecular assays was observed. The BD MAX MRSA assay proved to be a reliable alternative for a highly automated system to detect methicillin-resistant Staphylococcus aureus (MRSA) in patient nares samples. Methicillin-resistant Staphylococcus aureus (MRSA) is an important cause of community and hospital-acquired infections (1, 2). Screening for MRSA colonization to help id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Previous studies have addressed the laboratory efficiency of both platforms using earlier assay versions and have found discrepancies in the turnaround times depending on the number of assays processed and the maximum capacity of the instrument (13). Overall, the hands-on time requirements per sample with the two methods were found to be comparable in our experience.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Previous studies have addressed the laboratory efficiency of both platforms using earlier assay versions and have found discrepancies in the turnaround times depending on the number of assays processed and the maximum capacity of the instrument (13). Overall, the hands-on time requirements per sample with the two methods were found to be comparable in our experience.…”
supporting
confidence: 67%
“…However, the sequences of the primers and probes in the two assays are likely distinct, and the extraction processes rely on different principles. The performances of the assays of the previous generations have recently been found to be similar (13), but the release of updated versions warrants a renewed comparison. Moreover, the MRSA clones isolated in Europe and the United States are epidemiologically different and assay performances could be different (14,15).…”
mentioning
confidence: 99%
“…A number of molecular platforms have been evaluated for specific specimen types, including stool, and potential pathogens in clinical laboratory settings and have been shown to be highly sensitive and specific when compared to conventional methods [ 3 5 ]. The BD MAX platform has been evaluated for the detection of MRSA and more recently stool pathogens [ 8 , 9 ]. Recently, several investigators have recognized that beyond scientific validation, these platforms need to be evaluated for their impact on the operations and the time to reportable results in clinical laboratories [ 7 , 10 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity, specificity, and positive and negative predictive values of the assay were found as 84.3%, 99.2%, 88.4%, and 98.9%, respectively. In a report by Widen et al [12], BD MAX and Xpert MRSA assays were compared and good agreement (97.9%) was demonstrated. They concluded that the BD MAX MRSA assay was a reliable alternative automated system for the detection of MRSA from nares samples.…”
Section: Discussionmentioning
confidence: 96%